An Efficient Proposed Approach for Tracing of Moving Object in Wireless Sensor Network - Ray, Manas Kumar; Roy, Gitanjali (International Journal of Computer Sciences and Engineering, 2025)
Now a days wireless sensor network is a rapid growing area, are increasing in demand and widely deployed. Sensor communicates with other nodes in wireless manner and has ability of collecting, storing, transferring data with each other. Sensors have low power and low cost. Replace and remove of power in each sensor is very difficult. Due to power constraint decrease in energy constraint is a major research issue like localizing, tracking etc. Our proposed approach is to track the moving object accurately with reduce energy consumption of each sensor. Our proposed approach is to locate the position of moving object within an area. First we describe proposed clustering approach and then within the cluster, a cluster head (CH) is positioned. Then active cluster head is localized to get the current moving position of object through sensors. Within that time span the remaining sensors is standby mode so that energy is minimized. Current location of object is localized by trilateration algorithm. Lastly our proposed system shows the network stability and with less consumed sensors power.